Integrating Virtual Reality Visual Perimetry Into Clinical Practice: A Review of Devices, Applications, and Limitations (Canadian Eye Care Today, 2025)
Visual field testing has long been a cornerstone of glaucoma diagnosis, monitoring, and management. The evolution of perimetry, from the early Tangent screen formalized by Julius Hirschberg in the 1870s to modern standard automated perimetry (SAP) such as the Humphrey Visual Field Analyzer (HFA), has aimed to improve accuracy and accessibility. In the 1940s and 1950s, the Goldmann perimeter and Tübingen perimeter were developed, with the Goldmann retaining a limited but important role in specific clinical scenarios. The Tübingen perimeter is now rarely used. By the 1980s, automated perimetry had become the standard, leveraging computational advances to reduce human involvement while preserving the spatial testing strategies introduced by earlier kinetic methods. Devices such as the Humphrey and Octopus perimeters became widely adopted and remain in clinical use today. Among these, the HFA is widely regarded as the gold standard for automated visual field testing.Although the HFA is the gold standard for automated perimetry, it has well-known limitations.  The device is expensive, requires substantial physical space, and requires a trained technician to operate. Importantly, many patients find the test uncomfortable or frustrating and often dread the experience. It is rare to encounter a patient who enjoys visual field testing, and poor tolerance can lead to unreliable results. Nevertheless, perimetry remains a cornerstone of glaucoma care, offering functional insights not captured by structural imaging alone. Improving patient compliance and enhancing the test experience are therefore critical.